Penerapan Augmented Reality Sebagai Media Pengenalan Tuntunan Sholat di Madrasah Ibtidaiah Nurul Hidayah Berbasis Android (LPPM Universitas Dinamika Bangsa, 2017)
Madrasah Nurul Hidayah is an educational institutions that teaches the religion of islam, one the subject which madrasah Nurul Hidayah taught is the guidance of Shalat. The learning process in this madrasah is still using a book accompanied by the teacher. This research aims to implement Android-based augmented reality as a media for introduction of shalat guidance virtually as an alternative media. System development method which this research uses is a waterfall with UML as a modeling system. The software used for the development is Unity 3D that is combined with the Android SDK and Vuforia SDK. This application can display shalat movement animation in a 3D form and displayed in the virtual wolrd. From the test results it can be concluded that any module on the application have run well.